Characteristics of snags and forest structure in southern mistbelt forests of the Amatole region, South Africa. (28th February 2017) - Wilson, Amy‐Leigh; Bowker, Meyrick; Shuttleworth, Adam; Downs, Colleen T.
Abstract: Standing dead trees (or snags) are an important component of forest ecosystems, especially for tree cavity‐nesting vertebrate species, but their prevalence in South African forests remains under studied. Consequently, we investigated forest structure, and the presence and abundance of snags in six southern mistbelt forests in the Eastern Cape, South Africa. These forests have had varying levels of timber extraction over the past 150 years or more. We found snags were relatively rare in all six forests (<4.3% of trees sampled). Mean diameter at breast height (dbh) of snags ranged from 52 to 82 cm across the forests, with smaller snags in Kologha Forest and larger snags in Tyume Forest. A bimodal distribution of snag successional stages was found, with frequencies peaking at early and late stages, and few in the intermediate stages. Tree species diversity in the forests was relatively low (twelve–nineteen species across forests; only 28 species in total). There was no significant difference in dbh of trees between forests, with most occurring in the 20–29‐cm dbh size class. Future studies are required to identify trees that most likely support suitable cavities for tree cavity‐nesting bird species, and to determine cavity‐nester assemblage requirements in southern African forests.